Dual CEA/CD44 targeting to colorectal cancer cells using nanobody-conjugated hyaluronic acid-modified mesoporous silica nanoparticles with pH- and redox-sensitivity. Issue 11 (9th May 2022) - Fan, Xiying; Wang, Tingting; Han, Min; Gu, Yi; Sun, Guochuan; Peng, Xinying; Shou, Qinghui; Song, Haipeng; Liu, Wenshuai; Nian, Rui
Abstract : Mesoporous silica nanoparticles (MSNs) loaded with doxorubicin and then modified with hyaluronic acid (HA) and nanobody (DOX@MSNs-HA-11C12) is a pH- and redox-responsive drug delivery system, resulting in over 90% of LoVo cell apoptosis within 48 h. Abstract : Colorectal cancer (CRC) is the second leading cause of cancer death among all malignancies. Drug delivery targeting tumor surface receptors improve therapeutic effects and lower side-effects since they can increase the drug accumulation in target tissues and cellular uptake. In this study, we established a pH- and redox-responsive drug delivery system based on mesoporous silica nanoparticles (MSNs) for the delivery of the anticancer drug doxorubicin hydrochloride (DOX). In this drug delivery system, MSNs-NH2 were modified with hyaluronic acid (HA) to form a highly loaded anticancer drug core; they were further coated with 11C12, a nanobody against carcinoembryonic antigen (CEA) to form a guiding outer layer (DOX@MSNs-HA-11C12). The accurate localization of nanoparticles would be mediated by two targeting molecules HA and nanobody 11C12, which target the CD44 receptor and the proximal membrane end of CEA on the surface of CRC cells, respectively. The release amount of DOX observed from in vitro drug release profiles increased as follows: pH 7.4 < pH 6.8 < pH 5.4, and (pH 7.4 + GSH) < (pH 6.8 + GSH) < (pH 5.4 + GSH), illustrating that the drug release could be accelerated in a weakly acidic environment as well as in the presence of reduced glutathione (GSH). In vitro cytotoxicity experiments showed that MSNs-HA-11C12 nanoparticles exhibited good biocompatibility and safety. Drug loaded nanoparticles modified by dual targeting molecules HA and 11C12 (DOX@MSNs-HA-11C12) led to higher LoVo CRC cell apoptosis in vitro, compared with DOX@MSNs-NH2 and DOX@MSNs-HA. Confocal laser scanning microscopy and fluorescence spectrophotometry further confirmed that the dual-targeting system significantly enhanced the uptake of DOX@MSNs-HA-11C12 by LoVo cells and the internalization of DOX was the highest, followed by DOX@MSNs-HA, DOX@MSNs-NH2, and DOX, subsequently. In this study, the nanobody targeting CEA was combined with the HA targeting CD44 receptor for the first time, which proved that the dual CEA/CD44 formulation can promote a more accurate drug delivery mode for CRC cells, and provide a basis for subsequent drug development for treating CRC and related cancers.